General English Module Development at USN Kolaka - ., Roslina; ., Hanna; Lio, Asrun; ., Nasrul (International Journal of Membrane Science and Technology, 2023)
It was determined that teaching English a s a compulsory subject at USN Kolaka did not adequately assist the realization of the institution’s 2039 goal. In addition to the varying perceptions of lecturers’ professionalism among lecturers, it is a result of lack of standardized teaching materials. In order to provide standardized teaching materials, it was required to carefully to developed general English module based on the needs of students. To fulfill the needs, the researcher developed the learning module through MPI which is an adaptation model from Dick and Carey development model. This study showed that the product of this current study is able to used at USN Kolaka. However, further research is recommended for improvement.